PENINGKATAN KEMAMPUAN MENULIS TEKS PROSEDUR DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) MELALUI MEDIA INFOGRAFIS - Nur Kholijah Kholijah; Harry Andheska; Gigih Harpuas ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2025)
Writing procedural texts is one of the basic skills that students at various levels of education must master, especially in academic subjects. This study aims to improve students' procedural writing skills through a Culturally Responsive Teaching (CRT) approach combined with infographic media. The CRT approach enables learning that is relevant to students' cultural backgrounds, thereby increasing their engagement and understanding in the learning process. The method used in this study was classroom action research (CAR) conducted in two cycles. Each cycle involved planning, implementing actions, observation, and reflection. The results of the study showed a significant improvement in students' procedural text writing skills after the application of the CRT approach through infographic media. Students became more active, creative, and able to organise information systematically. In conclusion, the combination of a culturally responsive learning approach and the use of visual media such as infographics is effective in improving students' writing skills.